Costs of herpes zoster complications in older adults: A cohort study of US claims database. Issue 9 (21st February 2019) - Meyers, Juliana L.; Candrilli, Sean D.; Rausch, Debora A.; Yan, Songkai; Patterson, Brandon J.; Levin, Myron J.
Highlights: Reports of shingles, a painful vaccine-preventable disease, increase with age. Eye, skin and nerve complications occur in ∼10% of shingles cases. Added costs due to neurologic complications are the highest. Increased costs occur primarily in the first quarter after shingles diagnosis. Abstract: Background/Objectives: Herpes zoster (HZ) incidence increases with age, and the burden of HZ is expected to grow with aging of populations worldwide. We aim to determine the incremental healthcare resource utilization and associated costs of patients with common HZ-related complications other than postherpetic neuralgia (cutaneous, neurologic and ophthalmic) compared to uncomplicated HZ. Methods: We conducted a retrospective cohort study of commercial health insurance claims covering about 40 million immunocompetent individuals aged ≥50 years at study entry from all over the US, from 2008 to 2013, with follow-up for one year after HZ onset. All-cause healthcare resource utilization and direct healthcare costs were recorded and calculated from six months before until 12 months after HZ onset. The mean costs for HZ patients with complications were compared to the mean costs for patients with uncomplicated HZ. Multivariable regression analyses estimated mean incremental costs adjusted for demographics, comorbidities, type of complication and time period. Results: Over the five-year study period, 22, 948 HZ patients (60% women, median age 62 years) who experienced at least one of the selected complications were compared to 213, 232 patients (63% women, median age 61 years) with uncomplicated HZ. Overall, the mean annual incremental unadjusted costs for the patients with HZ-related complications were US$4716, ranging from US$2173 for ophthalmic to US$18, 323 for neurologic complications. Most of the incremental costs associated with HZ complications were accrued during the first quarter after HZ onset. For each complication type the incremental costs increased with age up to, but not including the oldest group, aged ≥80 years. Conclusions: Approximately 10% of immunocompetent older patients with HZ develop complications which considerably increase the economic burden of HZ. Vaccination of older adults will offset some of the burden of HZ, including costs associated with HZ-related complications.